Corresponding member of the USSR Academy of Sciences V. S. Troitskiy and his role in shaping the civic position of scientific community in Gorky region.1985–1991 - A. A. Fomenkov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the activities of corresponding member of the USSR Academy of Sciences V. S. Troitskiy stayed against the launch of the Gorky nuclear power plant for heat supply. V. S. Troitskiy’s arguments against starting this object are indicated. The reasons for the significance of his actions against GAST for the development of informal politicized organizations in Gorky are revealed. The influence of V. S. Troitskiy on the position of the scientific community on significant socio-political issues is indicated